ANALISIS WACANA LISAN PADA MAHASISWA ANTARDAERAH DI YOGYAKARTA - Syukriati, Syukriati (Universitas Wijaya Kusuma Surabaya, 2019)
This study aims to to study and analyze oral discourse in student funds reside in yogyakarta. Oral discourse that occur in the form of the use of intervening code ( code-switching ) by college students coming from java and outside java.Methods used is the method is to take a. the use of language. The subject of the research is a student who comes from several areas live in one. for lodging A technique used in the data collection techniques basic listening and engineering advanced slc (simak libat cakap) because researchers to participate or were directly involved in conversation and give the conversation. The result showed that the context of the talks is different from other regions of the students were could lead to the code in the intervening daily communication. With a code adopted code from intervening in the form of words and phrases.